Everolimus-Induced Oral Mucositis Can be Prevented by Hippophae Rhamnoides Extract in Rats - (:unkn) unknown (My University, 2021)
Objectives: Oral mucositis is a significant toxicity related to the mammalian target of rapamycin inhibitor everolimus. Oxidative stress and pro-inflammatory cytokines, which contribute to treatment-related mucositis, can betargeted with Hippophae rhamnoides extract (HRE). Herein, we assessed the effects of HRE on everolimus-inducedmucositis in rats.Methods: Eighteen rats were equally divided into healthy, everolimus, and everolimus plus HRE groups. Malondialdehyde (MDA) and total glutathione (tGSH) levels along with interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha(TNF-α) gene expression levels were measured in the tongue and buccal mucosa tissues of all groups, histopathologicalchanges were also evaluated. We tested the significance of variations with one-way variance analysis. We also analyzedthe differences between groups with Kruskal–Wallis test and Mann–Whitney U-test.Results: HRE significantly decreased MDA and increased tGSH levels and reduced IL-1β and TNF-α gene expression inboth tissues administered everolimus (p<0.001 for each). Histological examination revealed that HRE improved epithelial formation and keratinization, disrupted by everolimus, and alleviated everolimus-related mononuclear cell infiltration (p<0.05 for each).Conclusion: In light of these results, HRE may be a promising agent to manage oral mucositis caused by everolimus,given the lack of effective therapeutic options for this type of adverse event.